Biweekly gemcitabine plus S‐1 for locally advanced and metastatic pancreatic cancer: a preliminary feasibility study. (1st July 2015) - Wada, Keita; Sano, Keiji; Amano, Hodaka; Miura, Fumihiko; Toyota, Naoyuki; Ito, Hiromichi; Shibuya, Makoto; Ikeda, Yutaka; Kainuma, Masahiko; Takada, Tadahiro
Abstract Background Chemotherapy for unresectable pancreatic cancer should not only prolong survival but maintain quality of life, considering its limited life expectancy. To achieve these goals, biweekly gemcitabine plus S‐1 was assessed in the clinical practice setting. Methods Fifty‐two patients with either locally advanced or metastatic pancreatic cancer who received biweekly gemcitabine plus S‐1 as a first‐line anti‐cancer treatment were included in this study. Treatment delivery, toxicity, response, and survival were reviewed to assess the feasibility and efficacy. Results The completion rate of treatment delivery was 95.1%, with relative dose intensity of 97.1% for gemcitabine and 97.3% for S‐1. Overall, grade 3 or worse adverse events were rare, with hematologic toxicities occurring in 5.8%. The objective response rate was 30.8%, and more than a 50% reduction of CA19‐9 was observed in 77.1%. Surgical conversion was completed with a margin‐negative resection in four patients whose tumor had shrunk for at least 6 months. The median progression‐free and overall survivals were 10.4 and 18.2 months, respectively. Reduction of CA19‐9 was associated with longer survival. Conclusions Biweekly gemcitabine plus S‐1 may be a good alternative to current standard chemotherapies for unresectable pancreatic cancer with less toxicity and less treatment burden without losing efficacy.